Sporadic Intra-Abdominal Desmoid: A Rare Presentation as a Hepatic Mass - Shahana Gupta; Udipta Ray; Souvik Chatterjee; Sanjeev Kumar; Ayusman Satapathy; Shamita Chatterjee; Tamal Kanti Choudhury (Hindawi Limited, 2012)
We report an unusual presentation of a sporadic intra-abdominal desmoid tumour, possibly arising from the diaphragm, masquerading as a hepatic mass in a young female without any history of surgery or trauma. Histopathology ruled out a hepatic origin of the tumour as was inferred from pre- and intraoperative evaluation. Immunohistochemistry showed positivity of lesional fibroblastic cells for β-catenin and negativity for CD34, CD117, EMA, SMA, desmin, vimentin, cytokeratin, and ALK1 thereby confirming the diagnosis of a desmoid tumour. There exist only a few reports in the literature on desmoids related to the diaphragm, but only one on a diaphragmatic desmoid that is possibly primary.